Evaluating massage therapy for radiation-induced fibrosis in rats: preliminary findings and palpation results - Geoffrey M. Bove; Holly McMillan; Mary F. Barbe (Cancer Biology & Therapy)
Radiation-induced fibrosis (RIF) is a common side effect of cancer treatment, but can manifest into a devastating syndrome for which there is no preventive measure or cure. In rats who perform a repetitive work task, who left untreated develop signs and symptoms that resemble repetitive motion disorders in humans, we have shown that manual therapy prevents the development of fibrosis and other key biomarkers. The fibrosis of RIF and repetitive motion disorders has similar biomarkers. In rats, we sought to determine if manual therapy would alter key biomarkers of post-irradiation fibrosis following X-ray irradiation given to the rat forelimb. One limb of rats was given a damaging dose of X-ray irradiation. Some limbs were massaged using a protocol previously described and characterized. Serum inflammatory markers, histological assays of tissue fibrosis and nerve pathology, and electrophysiology for neuropathic discharge were assayed after 8 weeks. We also tested if an experienced therapist could identify the irradiated limb using blinded palpation at the 8 week end-point. While preliminary assays showed robust changes compared to control limbs, the other assays did not show similar pathology. Our therapist could detect each irradiated limb. Serum inflammatory markers were reduced by massage to the irradiated limb. We conclude that blinded palpation is sensitive to detect subtle changes in tissue following irradiation. In contrast to the preliminary studies, the dose of irradiation used was insufficient to induce long-lasting deep fibrosis or nerve degeneration. We suspect that a difference in housing, and thus physical activity, was the plausible reason for this difference.